The Sun and How to Observe It - Jenkins, Jamey L. (Springer, 2017)
Chapter 1:The Sun, Yesterday and Today. Chapter 2: Some Basics of Solar Observing. Chapter 3: Observing the White Light Sun. Chapter 4: White Light Solar Features. Chapter 5: Recording White Light Observations. Chapter 6: Observing the Monochromatic Sun. Chapter 7: Monochromatic Solar Features. Chapter 8: Solar Photography. Chapter 9: Where do You Go from Here?